Various injury patterns due to combustion (typical but unfamiliar to physicians and easy to miss) in Korea: a case report - Hyung Il Kim (Journal of Trauma and Injury)
Patients transported from fire sites may exhibit various injury patterns. Major trauma, skin burn, inhalation burn, and carbon monoxide poisoning are typical injuries. However, most physicians may be unfamiliar that cyanide poisoning can frequently occur due to combustion. Cyanide poisoning is highly significant owing to high mortality and the existence of antidotes. I present a 35-year-old man who was transported from a burning building and suffered severe metabolic acidosis despite no major bleeding as well as mild carbon monoxide poisoning. I suspected cyanide poisoning and administered the antidote; subsequently, the patient showed improvement. The next day, sudden airway obstruction developed, and emergency endotracheal intubation was performed. The inhalation damage was detected only in the lower airway tract and not in the upper airway. Physicians should be aware of cyanide poisoning and inhalation burn to avoid missing treatment opportunities.